Uji Sensitifitas Rapid Test Malari Menggunakan Sampel yang Diencerkan Secara Berseri - Khaerul Ikhwan; Pahmi Husain; Baiq Naili Dewi Atika; Sri Muji Rahayu; Hermaningsih Hermaningsih (EVOLUSI: JOURNAL OF MATHEMATICS AND SCIENCES, 2021)
Malaria is an infectious disease that is spread by Anopheles mosquitoes infected by plasmodium malaria. This study raised the problem of how high the sensitivity of the malaria quick test by using samples was signifycuously carried out at the Mataram general hospital clinic laboratory. this study uses the experimental method by dilution of radiant to find out the sensitivity of the marine test rapid that was stated positively infected by right Plasmodium falciparum with the results of the examination found two people with the plasmodium falciparum (+) 1 with catch positive on dilution 1/5,1/10,1/20. Plasmodium falciparum (+) 2 with each positive o dilution 1/5, 1/10, 1/20, 1/20, 1/40, 1/80. Plasmodium falciparum (+) 3 with each positive on dilution 1/5, 1/10, 1/20, 1/40, 1/80, 1/160, 1/320. Plasmodium falciparum (+) 4 with each positive on dilution 1/5, 1/10, 1/20, 1/40, 1/80, 1/160, 1/320, 1/640, 1/1280.